Imagining a New Society Through Applied Theatre - Tuğçe Gözde Pelister (Konservatoryum)
This article aims to understand and discuss applied theater in terms of its definition, scope, and potential for creating social change, and to present suggestions in this context. Essentially, applied theater is a theater practice that is applied to selected target groups or communities, and with participants are being expected to exhibit the expected change and improvement. Unfortunately, examples of applied theater in Türkiye are limited, but significant examples are found in countries such as America, Hong Kong, England, and even Uganda. Türkiye has always had characteristic social conditions, particularly in this century, and significant social, identity, and class divisions have emerged here. Discussing whether communities can be the carriers of a new society through applied theater, by starting with specific groups in the face of inadequate or non-beneficial state policies will strengthen hope for the future. In this context, this study reveals whether applied theater provides objective results that can turn this hope into reality.